Assessment and Spatial Distribution of Mineral Groundwater Quality in Ardabil Province, Iran - Azizi 1, Nasrin; Seifi Binalloo 2, Rasoul; Habibi Marasht 2, Reza; Soleymani 3, Mohammad; Roudbari 4*, Aliakbar (Shahroud Journal of Medical Sciences, 2018)
Background: The present study was conducted to determine the quality of mineral ground waters and analyze their spatial distribution in Ardabil Province of Iran.Methods: This descriptive analytical study was carried out on natural mineral water wells in Ardabil Province over one year. Samples of water were taken from a total of 44 wells in this province every season, from April 2016 to February 2017. They were then transferred to Khak Azmay-e Moghan Laboratory and their Total Dissolved Solids (TDS), chloride, calcium, magnesium, sulfate, sodium and bicarbonate were measured based on the instructions presented in Standard Methods. The Ground Water Quality Index (GWQI) was then determined based on the measured parameters. The spatial distribution of the ground waters based on the GWQI was then also determined in a Geographic Information System (GIS).Results: The GWQI varied extensively in the natural mineral water wells of Ardabil Province, from 24.88 to 312.58. The best physicochemical quality based on the GWQI was observed in Hammam-e Sangi and the poorest quality in Saghezji-Mardaneh. According to the index, 2.5% of the wells were of very good quality, 30% were of good quality, 32% of moderate quality, 13.5% of poor quality and 22% were of inappropriate quality.Conclusions: According to the results, the most important quality problems included high levels of TDS, chlorine and sulfate and low pH values. Considering that these wells supply people’s drinking water in this region, consumers should be warned of their water quality, and purification procedures should also be carried out to allow the hygienic use of these valuable resources.